PENGARUH PENERAPAN SISTEM MOVING CLASS TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA JEPANG DI SMA CENDANA PEKANBARU - Suri, Intan; Yanti, Yanti; Oktavia, Devi Haryanti; Aini, Syarifa (Jurnal Manajemen Pendidikan, 2020)
Various types of learning systems are implemented in schools depending on their respective policies. SMA Cendana Pekanbaru is one of the schools that uses a moving class learning system in the teaching and learning process. With this system, it is expected to improve the quality of the teaching and learning process, to increase student motivation and also to achieve student learning outcomes. The moving class system is a teaching and learning system characterized by students visiting the teacher in class. The purpose of this study was to find out how the moving class system was applied at Cendana High School Pekanbaru and how it affected students' learning motivation in Japanese subjects. This research is a descriptive research with the research subject is class XII students who take Japanese language specialization hours as many as 9 people. Data were taken by means of interviews, observations, documentation and questionnaires and then analyzed and drawn conclusions. The results of the analysis show that the teaching and learning process using the moving class system at SMA Cendana Pekanbaru has been going well and the moving class has a positive effect on students' learning motivation